1994
DOI: 10.1002/jmri.1880040521
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo evaluation of ferromagnetism, heating, and artifacts produced by heart valve prostheses exposed to a 1.5‐T MR system

Abstract: Ex vivo testing techniques were used to determine the ferromagnetic qualities of, presence of heating in, and artifacts produced by 13 different heart valve prostheses exposed to a 1.5-T (64-MHz) magnetic resonance (MR) system. None of the heart valve prostheses showed a measurable deflection in the 1.5-T static magnetic field. Only minimal artifacts were produced during MR imaging with a fast spoiled GRASS (gradient-recalled acquisition in the steady state) pulse sequence. The largest temperature changes meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11] However, burn accidents caused by MR procedures have been reported. [12][13][14] The mechanism of RF irradiation-induced heating of human body implants is complicated and in‰uenced by quality of material and shape of the implant, body weight and height, electrical properties of various internal organs, thermoregulatory reaction, blood ‰ow, and other parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] However, burn accidents caused by MR procedures have been reported. [12][13][14] The mechanism of RF irradiation-induced heating of human body implants is complicated and in‰uenced by quality of material and shape of the implant, body weight and height, electrical properties of various internal organs, thermoregulatory reaction, blood ‰ow, and other parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the reported force of implants in [27] provides a good reference. This study found that forces above 1 gF can be considered as high in terms of safety because the end effector of the actuated robot may come in contact with critical tissues during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Many heart valve prostheses and annuloplasty rings have been evaluated to determine whether they are acceptable for patients undergoing MR examinations with scanners operating at 1.5 T or less. 3,43,48,49,51 Of these, several displayed measurable yet relatively minor magnetic field interactions in relation to the static magnetic fields of the MR systems used for testing. The forces exerted on these valves and rings are less than the forces exerted by gravity and considerably less than those exerted by the beating heart and resultant pulsatile blood flow (Ϸ7.2 N).…”
Section: Prosthetic Heart Valves Annuloplasty Rings and Sternal Sutmentioning
confidence: 99%
“…These studies indicated that temperature increases are relatively minor, with studies reporting heating ranging from 0°C to 0.8°C. 48,49,51,54,55 As with vascular stents, any heating is likely to be somewhat dissipated by flowing blood. Although there is a theoretical possibility of an electromagnetic interaction with a heart valve that contains metal in the disk or leaflet that could inhibit opening and closing of the mechanical heart valve prosthesis (referred to as the Lenz effect), this has never been demonstrated experimentally or reported clinically.…”
Section: Prosthetic Heart Valves Annuloplasty Rings and Sternal Sutmentioning
confidence: 99%